Government Investment: Review of Regional Revenue and Central Government Allocation Funds for Regional Development - Mas Nur Mukmin; Indra Cahya Kusuma; Farizka Susandra; Noprizal Dharmawan (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: This study aims to examine the role of regional and central government through general allocation funds in making capital expenditures oriented to public services. The research conducts in the West Java Province, Indonesia by analyzing the financial reports of the local government of Bogor City, Depok City and Bekasi City for 10 years, from 2008 to 2018. Design/methodology/approach: Hypothesis testing carries out using multiple linear regression. Findings: This research succeeds in revealing that regional autonomy in managing regional revenue increased the government capital spending. The involvement of the central government also plays an important role in regional development through general allocation funds. Research limitations/implications: This shows that local governments are still very dependent on the availability of funds to meet public needs. Practical implications: Economic aspects in investment decisions could not be fully applies, especially considering the rate of return on investment. So that with the available funds, the government still prioritizes social and cultural aspects in performing public services through capital expenditures. Originality/value: The research explored the unrevealed value from technical financial report aspects that affect the government investment. Paper type: Research paper.